Identification of F‐box only protein 7 as a negative regulator of NF‐kappaB signalling - Kuiken, Hendrik J.; Egan, David A.; Laman, Heike; Bernards, Rene; Beijersbergen, Roderick L.; Dirac, Annette M. (Journal of cellular and molecular medicine, 2012)
The nuclear factor κB (NF‐κB) signalling pathway controls important cellular events such as cell proliferation, differentiation, apoptosis and immune responses. Pathway activation occurs rapidly upon TNFα stimulation and is highly dependent on ubiquitination events. Using cytoplasmic to nuclear translocation of the NF‐κB transcription factor family member p65 as a read‐out, we screened a synthetic siRNA library targeting enzymes involved in ubiquitin conjugation and de‐conjugation for modifiers of regulatory ubiquitination events in NF‐κB signalling. We identified F‐box protein only 7 (FBXO7), a component of Skp, Cullin, F‐box (SCF)‐ubiquitin ligase complexes, as a negative regulator of NF‐κB signalling. F‐box protein only 7 binds to, and mediates ubiquitin conjugation to cIAP1 and TRAF2, resulting in decreased RIP1 ubiquitination and lowered NF‐κB signalling activity.